PEMAHAMAN KONSEP PREDESTINASI SEBAGAI JAMINAN KESELAMATAN BERDASARKAN ROMA 8:29-30 - Sonny Herens Umboh (Sekolah Tinggi Teologi Arastamar Bengkulu, 2023)
Salvation is something that is fundamental to the faith of believers, even though there are still often differences in understanding of salvation. There are those who argue that salvation can be obtained because of contributions from actions or responses from humans who are trying to get it. For those who hold the understanding of predistination, safety is an absolute guarantee for everyone He has chosen. Although the concept of predistination is often considered unbiblical, through this research using a qualitative approach based on Romans 8:29-30 it is hoped that it can provide an understanding of that salvation so that through the concept of predistination it can provide an understanding that can guarantee that salvation and is a biblical thing.